Threshold of erosion of submarine bedrock landscapes by tidal currents. Issue 6 (14th November 2012) - Mitchell, Neil C.; Huthnance, John M.; Schmitt, Thierry; Todd, Brian
ABSTRACT Since sea level stabilized 7000 yr bp, shelf seas experiencing semi‐diurnal tides will have been affected by streaming four times per day. If tidal erosion of bedrock were even only marginally efficient, the ~10 million streamings since then should have left geomorphological imprints. We examine high‐resolution multibeam sonar data from three areas with extreme tidal currents. The Minas Passage (Bay of Fundy) experiencing 8‐knot surface tidal currents was surveyed in 2007 with a multibeam sonar. In an area near to transverse dunes, which are evidence for bedload transport, the data show local overhanging surfaces near to the sediment‐rock contact, potentially created by abrasion by saltating particles. However, they are uncommon. In the Straits of Messina, where surface currents reach 10 knots, surveying revealed ridges lying oblique to the flow that are not obviously broken into separate outcrops by erosion. In the Bristol Channel, UK, sonar data collected where currents reach 3·4 knots at 1·5 m above the bed reveal outcrops of limestone with superimposed sand dunes, but only minor rounding of blocks. Holocene tidal currents have apparently been generally ineffective at eroding bedrock. We examine this issue further by compiling extreme tidal streams around the UK and from them estimate shear stresses, representing a macro‐tidal environment where peak surface currents reach 9·7 knots. Those data are compared with shear stresses in mountainous rivers where long‐term rates of erosion are comparable with tectonic uplift rates and are thus geomorphologically significant. Whereas river stresses reach 102–103 Pa, the largest tidal stresses are generally 101 and only rarely approach 102 Pa, too small for quarrying to operate generally. However, the vertical faces in the Minas Passage may represent the onset of abrasion. Given this limited evidence for abrasion, we explore conditions in the geological past for tides that may have locally eroded bedrock. Copyright © 2012 John Wiley & Sons, Ltd.